PENGARUH PEMBERIAN FORMULA KOMBINASI AIR JERUK NIPIS (Citrus aurantifolia) DENGAN TEPUNG DAUN KELOR (Moringa oleifera) TERHADAP KADAR LEUKOSIT PADA TIKUS SPRAGUE DAWLEY (Rattus norvegicus) DISLIPIDEMIA - Bintanah, Sufiati; Sari, Dewi Kartika; Latrobdiba, Zahra Maharani; Nadia, Fika Shafiana (Persagi, 2023)
Dyslipidemia can trigger inflammation that affects the activity and number of leukocytes. Inflammation can be improved with foods that contain anti-inflammatories such as lime and Moringa leaf powder. This study aims to determine the effect of giving a combination formula of lime juice and moringa leaf powder on leukocyte levels in dyslipidemic Sprague Dawley rats. Experimental study with Randomized Pre and Post Test with Control Group Design. Samples were divided into 4 groups P0 (control group), P1 (2.25 ml lime + 0.2 g moringa), P2 (1.57 ml lime + 0.26 g moringa) and P3 (2.92 ml orange lime + 0.14 g moringa) were given intervention for 21 days. The results showed that there was no significant decrease in leukocyte levels after being given intervention in each group with a p-value> 0.05. So it can be concluded that giving the combination formula did not affect the decrease in leukocyte levels.